Pengaruh Kecerdasan Emosi dan Kontrol Diri terhadap Cyberbullying pada Siswa di MTs Ma’arif Temanggung - Anang Setiya Budi; Eko Nusantoro (Neolectura, 2022)
This research was motivated by the phenomenon of a preliminary study on cyberbullying at MTs Taaruf Temanggung which showed that they had done cyberbullying. The purpose of this study was to obtain correct data regarding the level of cyberbullying, emotional intelligence, self-control, and the influence between these variables. The design of this research is ex post facto research with correlational research type. The data collection tool uses cyberbullying scale, emotional intelligence scale, and self-control scale. Validity test using construct validity. While the reliability test uses the Cronbach alpha formula. The results of the descriptive analysis showed that the average student cyberbullying was in the high category, the average student's emotional intelligence was in the medium category, and the average student social support was also in the medium category. The results of simple regression analysis show that there is a significant negative effect between emotional intelligence on cyberbullying and also between self-control and cyberbullying. Furthermore, the results of multiple regression analysis also showed a significant negative effect between emotional intelligence and self-control on cyberbullying. So it can be concluded that the level of emotional intelligence and self-control affect the level of cyberbullying of students